Pendekatan Usability Testing untuk Mengukur Penggunaan SIAKAD di Poltekkes Palembang - Basyuni, Muhamad Chasan; Oktaviani, Nia (JUSIFO : Jurnal Sistem Informasi, 2023)
Sistem Informasi Akademik (SIAKAD) of Poltekkes Palembang is designed to facilitate the management of academic activities and the dissemination of information to users, including lecturers and students, in a structured and integrated manner. This research aims to measure the usage of SIAKAD at Poltekkes Palembang through usability testing. Additionally, the research also identifies shortcomings in the layout of SIAKAD, such as the presence of invalid or outdated information. The test results indicate that the majority of users are able to operate SIAKAD effectively. Furthermore, the measurement results show that the learnability, efficiency, memorability, errors, and satisfaction of SIAKAD overall reach a good level. Thus, SIAKAD plays a significant role in supporting academic activities at Poltekkes Palembang. Nevertheless, there is still room for improvement in the usage of SIAKAD. With a deeper understanding of the aspects that need to be addressed in SIAKAD, institutions can take appropriate actions to enhance user experience.